Pemberdayaan UMKM Melalui Tata Kelola Terpadu Pasar Rakyat Terintegrasi Pesantren Ngalah Purwosari, Pasuruan - Dayat, M.; Sukamto, Sukamto (Humanist Journal, 2024)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) through the management of integrated pesantren community markets in Purwosari District, Pasuruan, aims to enhance local economic welfare and create a more organized market environment. This program involves collaboration between pesantren, the village government, and local communities to relocate MSMEs, which were previously selling on the roadside, to a more structured market. The provided assistance includes training on digital marketing, product quality improvement, and integrated market management. As a result, the program successfully increased market access for MSMEs, improved product quality, and expanded market reach through digital technology. This integrated pesantren community market not only created an ecosystem that supports local economic growth but also made a positive contribution to community-based economic empowerment.